Development of the SIDEM Application (Advanced Village Information System) as an Administrative Management System for Kedawung Village - Marita Qori’atunnadyah; Aris Slamet; Ahmad Hidayatul Kabir; Mohammad Hasan (Journal of Informatics Development, 2023)
PPK Ormawa is a community service and empowerment program initiated by student organizations. In particular, PPK Ormawa HMJ Informatics at the Widya Gama Lumajang Institute of Technology and Business devised SIDEM, a village administration system for Kedawung Village. SIDEM utilizes Agile methods, allowing swift and successful software development. The system's outcome is a user-friendly design benefiting both village officials and communities. The application of Agile methods facilitated flexibility, promptly adapting to evolving requirements and incorporating feedback. This approach ensured the system's functionality while aligning with Kedawung Village's specific needs. Agile's rapid development further enabled timely implementation, potentially significantly improving village administration and communication. SIDEM's design emphasis on usability demonstrates a commitment to user-centered development, empowering local stakeholders. Ultimately, the success of SIDEM's Agile-driven development underscores the significance of agility and user-centric design in community service initiatives. This model serves as a valuable example for future technology-based community empowerment projects.